Metabolically healthy obesity and cardiovascular events: A nationwide cohort study. Issue 11 (2nd August 2021) - Fauchier, Grégoire; Bisson, Arnaud; Bodin, Alexandre; Herbert, Julien; Semaan, Carl; Angoulvant, Denis; Ducluzeau, Pierre Henri; Lip, Gregory Y. H.; Fauchier, Laurent
Abstract: Aim: To evaluate the associations between metabolically healthy obesity (MHO) and different types of incident cardiovascular events in a contemporary population. Materials and Methods: All patients discharged from French hospitals in 2013 with at least 5 years of follow‐up and without a history of major adverse cardiovascular event (MACE; myocardial infarction, heart failure [HF], ischaemic stroke or cardiovascular death [MACE‐HF]) or underweight/malnutrition were identified. They were categorized by phenotypes defined by obesity and three metabolic abnormalities (diabetes, hypertension and hyperlipidaemia). Hazard ratios (HRs) for cardiovascular events during follow‐up were adjusted on age, sex and smoking status at baseline. Results: In total, 2 873 039 individuals were included in the analysis, among whom 272 838 (9.5%) had obesity. During a mean follow‐up of 4.9 years, when pooling men and women, individuals with MHO had a higher risk of MACE‐HF (multivariate‐adjusted HR 1.22, 95% confidence interval [CI]: 1.19‐1.24), new‐onset HF (HR 1.34, 95% CI 1.31‐1.37) and atrial fibrillation (AF; HR 1.33, 95% CI 1.30‐1.37) compared with individuals with no obesity and zero metabolic abnormalities. By contrast, risks were not higher for myocardial infarction (HR 0.92, 95% CI 0.87‐0.98), ischaemic stroke (HR 0.93, 95% CI 0.88‐0.98) and cardiovascular death (HR 0.99, 95% CI 0.93‐1.04). MHO in men was associated with a higher risk of clinical events compared with metabolically healthy men of normal weight (HR 1.12‐1.80), while women with MHO had a lower risk for most events than metabolically healthy women of normal weight (HR 0.49‐0.99). Conclusions: In a large and contemporary analysis of patients seen in French hospitals, individuals with MHO did not have a higher risk of myocardial infarction, ischaemic stroke or cardiovascular death than metabolically healthy individuals with no obesity. By contrast, they had a higher risk of new‐onset HF and new‐onset AF. However, notable differences were observed in men and women in the sex‐stratified analysis.